The Effects of Stigma on Mental Health Nurses: A study at Ankaful Psychiatric Hospital - Sampson Opoku Agyemang; Jerry Paul Ninnoni (University of Cape Coast, 2019)
Society’s perception of the causes of mental disorder is one of the factors that influence how thementally ill is treated. Stigma affects not only people with mental illnesses but nurses and other professionals working with individuals diagnosed with mental illness. This study assessed the effect of stigma on mental health nurses. A cross-sectional descriptive design was adopted for this study, and a structured questionnaire was used to collect data from 101 mental health nurses. Data was analyzed and summarized descriptively using frequency tables and graphs. An inferential analysis was conducted by Pearson Product Moment of correlation and Independent sample t test. The results show that the respondents perceive stigma to stem largely from the society. Females reported a higher level of stigma and discrimination from the general public than males. The majority of the participants view stigma as discrimination. Public education and expansion of community care are important measures to reduce the effects of stigma and discrimination
20p,; ill
Keywords: mental illness; mental health nurses; help seeking behavior